RELATIONSHIP BETWEEN STAFF COMPETENCY AND IMPLEMENTATION LEVEL OF PUBLIC PROCUREMENT REGULATORY FRAMEWORK IN THE DEVOLVED GOVERNMENTS IN KENYA - Matunga, Denish Ateto; Ngugi, Patrick Karanja; Odhiambo, Romanous (International Journal of Supply Chain Management, 2021)
Purpose: The purpose of this study was to analyse the relationship between staff competency and implementation level of public procurement regulatory framework in the devolved governments in Kenya. Methodology: The study used descriptive design. The population targeted was 47 devolved governments in Kenya. The study adopted census because of the small size of the population. A structured questionnaire was used as a data collection tool. The study also undertook a pilot test on the instrument's reliability and validity in the 3 counties; Nyamira, Kisii, Homa-Bay Counties where nine (9) respondents were engaged in the pilot study. Cronbach's co-efficient Alpha and confirmatory factor analysis (CFA) were used to measure the reliability and validity respectively. The data was cleaned and coded then entered into SPSS 25 to be analyzed. The use of descriptive and inferential statistics for data analysis was considered. Study engaged the key informers from the 44 county Governments who positively responded hence achieving 100% response rate. The statistical tests were also done in the study. Presentation of data was in form of charts and tables as deemed appropriate. The study also used ANOVA to analyze the degree of relationship between the variables in the study. Results: The findings of the study indicate that there was a positive significant relationship between Procurement Staff Competency and implementation level of public procurement regulatory framework in the devolved governments in Kenya. The findings were found to be significant as the p-value of 0.00000 which was less than 0.05. This means that Procurement Staff Competency significantly affects positively Implementation level of public procurement regulatory framework in the devolved governments in Kenya. The findings therefore, implied that procurement staff competency was an important factor in determining the level of implementation of public procurement regulatory framework in the devolved governments in Kenya Unique contribution to theory, practice and policy: The study recommended the adoption of procurement staff competency as a way of improving the implementation level of public procurement regulatory. The study therefore, recommended that the county government to heavily invest on procurement staff capacity building as an important factor in improving the level of implementation of public procurement regulatory framework in devolved governments in Kenya. Since some staff members lacked technical skills beyond secondary education, the study recommended that the county governments need to identify, support and organize in-service training for the procurement staff officers to improve on their knowledge and skills capacity. The study found out that Competency theory model was applicable in the study and can provide more knowledge to future researchers and scholars.